2022
DOI: 10.1038/s43856-022-00110-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure impacts adaptive therapy by shaping intra-tumoral competition

Abstract: Background Adaptive therapy aims to tackle cancer drug resistance by leveraging resource competition between drug-sensitive and resistant cells. Here, we present a theoretical study of intra-tumoral competition during adaptive therapy, to investigate under which circumstances it will be superior to aggressive treatment. Methods We develop and analyse a simple, 2-D, on-lattice, agent-based tumour model in which cells are classified as fully drug-sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 79 publications
3
38
0
Order By: Relevance
“…However, it is not the number of metastases that matters, but the largest lesions that dominate the dynamics. Larger metastases have longer cycles, while smaller metastases have quicker cycles, similar to findings where more spread out tumor seeds had faster cycles than larger patches of cells in [18]. We also found that more drug resistance slows the treatment cycles, as expected, and a faster cell turnover speeds up drug response time by increasing the surface area to aid in drug penetration but slows the regrowth time by reducing the net proliferation rate.…”
Section: Discussionsupporting
confidence: 86%
“…However, it is not the number of metastases that matters, but the largest lesions that dominate the dynamics. Larger metastases have longer cycles, while smaller metastases have quicker cycles, similar to findings where more spread out tumor seeds had faster cycles than larger patches of cells in [18]. We also found that more drug resistance slows the treatment cycles, as expected, and a faster cell turnover speeds up drug response time by increasing the surface area to aid in drug penetration but slows the regrowth time by reducing the net proliferation rate.…”
Section: Discussionsupporting
confidence: 86%
“…To improve the accuracy of tumor burden assessment, we are expanding this model to incorporate clinical PSA, testosterone, imaging data, histology data on AR and Cyp17 immunohistochemistry and genomic data on ctDNA, AR amplification and mutations in ctDNA. New models to incorporate spatial heterogeneity are also being used to analyze the trial data [ 30 , 31 ]. Due to the small sample size and lack of long term follow up, we have not detected statistically significant associations between duration of adaptive therapy with Gleason score, choice of NHA (cyp17 inhibitor vs. AR antagonist), mCSPC status (de novo vs. recurrent, high-risk vs. non high-risk).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it slows down the rate at which cancer cells gain resistance with a prolonged treatment-free period owing to reduced drug exposure [39][40][41][42][43][44][45]. In contrast, the lack of prolonged treatment-free time during the continuous administration of a drug, such as sotorasib or adagrasib, results in an increased rate of cancer cells acquiring resistance mutations and prevents patients from achieving a complete response to a drug [46,47]. In the long run, this strategy has the potential for KRAS patients to be given the same treatment for a longer period, safely maintaining a safe tumour burden that is financially feasible for patients and increasing progression-free survival [48].…”
Section: Clinical Evidence Of Adaptive Therapymentioning
confidence: 99%